2021
DOI: 10.1177/15266028211047946
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Diameter Evaluated by Intravascular Ultrasound Versus Angiography

Abstract: Purpose: Although reference vessel diameter (RVD) is conveniently measured by angiography during femoropopliteal (FP) endovascular therapy (EVT) in clinical practice, angiography will potentially underestimate RVD. On the other hand, intravascular ultrasound (IVUS) can measure RVD precisely. The aim of this study was to reveal the difference between angiography- and IVUS-assessed RVD in patients undergoing FP-EVT for symptomatic peripheral artery disease (PAD). Methods: We analyzed a prospective and multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It has been reported that there is a discrepancy in vessel diameter by approximately 1 mm between IVUS and angiography; this discrepancy is marked in small vessels. 25 The use of IVUS may provide adequate dilatation. 26 In addition to CTO and circumferential calcification, postprocedural IVUS‐measured minimal lumen area has been reported to be a significant predictor of restenosis after DCB.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is a discrepancy in vessel diameter by approximately 1 mm between IVUS and angiography; this discrepancy is marked in small vessels. 25 The use of IVUS may provide adequate dilatation. 26 In addition to CTO and circumferential calcification, postprocedural IVUS‐measured minimal lumen area has been reported to be a significant predictor of restenosis after DCB.…”
Section: Discussionmentioning
confidence: 99%
“…The vessel diameter measured using IVUS is generally larger than that measured in angiography. 22 Consequently, IVUS use would be associated with the use of larger balloons, resulting in aneurysmal degeneration formation. Although it is still unclear whether aneurysmal degeneration after FP-DES implantation affects clinical events, a case of aneurysmal degeneration progression has been reported, 23 and long-term follow-up is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…10,14 However, the reference vessel diameter measured by IVUS has been reported to be larger than that measured by angiography, and larger balloon selection might lead to POCs, such as peripheral embolism and vascular rupture. 18 In addition, it has been reported that complications increase with procedural time extension. 12 The current study revealed a lower rate of major amputation, a higher rate of vessel rupture, and longer operation time in the IVUS group than in the non-IVUS group.…”
Section: Ivus and Pocsmentioning
confidence: 99%